Second Five Year Plan District Plan 1958-59 Cuddapah District - Planning Commission (Planning Commission, 1958)
The Kurnool-Cuddapah Canal is the chief irrigation source of the district. It takes off from an anicut over the Tungabhadra, built at 17 miles above the town of Kurnool and is 190 miles long. It enters the Cuddapah district at the north-eastern corner of Jammalamadugu taluk at its 137th miles and flows through Predator and Cuddapah taluks terminating at Patha Cuddapah tank. There are several distributaries from the canal. The canal crosses the Pennar by means of other sources of irrigation. The river channels have open heads and water is diverted into them by means of temporary sand dams and channels in the river beds constructed by the ryots. Irrigation from wells is also resorted to in some areas.
Planning and Development Department Andhra Pradesh
Planning and Development Department Andhra Pradesh